Reasonable deep application of sheep manure fertilizer to alleviate soil acidification to improve tea yield and quality - Jia, Xiaoli; Wang, Yuhua; Zhang, Qi; Lin, Shaoxiong; Zhang, Ying; Du, Mengru; Chen, Meihui; Ye, Jianghua; Wu, Zeyan; Wang, Haibin (Frontiers in Plant Science, 2023)
Soil acidification in Chinese tea plantations is widespread, and it has significantly affected the growth of tea trees; it was important to explore soil remediation of acidified tea plantations in depth for the sustainable development of tea industry. In this study, the effects of sheep manure fertilizer with different application depths on soil acidification, tea yield and quality, and soil nitrogen transformation in tea plantations were analyzed for five consecutive years from 2018 to 2022. The results showed that long-term use of sheep manure fertilizer significantly reduced soil acidification (P < 0.05) in tea plantations, improved soil pH and soil ammonium nitrogen content, enhanced root activity and root nitrogen uptake capacity of tea trees, and thus improved tea yield and quality. The effect of different application depths of sheep manure fertilizer on tea yield and quality was mainly reflected in the transformation ability of soil ammonium nitrogen and nitrate nitrogen, which showed that high transformation ability of soil ammonium nitrogen and high ammonium nitrogen content were beneficial to high tea yield and vice versa, and the best effect was achieved when sheep manure was applied at a depth of 50 cm and 70 cm. The topsis analysis confirmed that sheep manure fertilization had a greater effect on root activity, ammonium nitrogen, ammonia intensity, and nifH gene. This study provided an important practical basis for the restoration of acidified tea plantation soil through sheep manure fertilizer management.